Wisdom in the Worldview of a Lithuanian - Smetonienė, Irena; Ganusauskaitė, Beatričė (Problemos, 2019)
[full article and abstract in Lithuanian; abstract in English]By using cognitive definition method created by the Lublin ethnolinguists, this paper aims to explore the Lithuanian conception of wisdom and where it stands within the set of moral values. Firstly, the data from various dictionaries is examined. The second part analyses data from a survey and represents the contemporary worldview of a young person. The third part is an analysis of data from six discourses, revealing wisdom as a complex concept. In the end, the cognitive definition is formulated. It reflects the understanding, evaluation, and characterization of wisdom in Lithuanianʼs mind, together with its coherence to other values and virtues.
Keywords: wisdom; concept; discourse; ethnolinguistics; philosophy